Identifying the Traditions and Culture of The Osing Tribe in Kemiren Village, Banyuwangi Regency as A Supplement to Social Geography Learning - Rully Ardiansyah; Tria Listari; Muhammad Syahidin (International Journal of Geography, Social, and Multicultural Education, 2024)
This journal examines the traditions and culture of the Osing tribe which is centered in Kemiren Village, Glagah District, Banyuwangi Regency, as supplementary material in learning Social Geography. The research methods used were participant observation, in-depth interviews, and document analysis. The research results show that the Osing tribe has a rich cultural heritage, including agricultural systems, traditional ceremonies and traditional arts. Geographical factors such as topography and climate also influence the life patterns of the Osing people. This study provides an in-depth understanding of the relationship between tradition, culture and the geographical environment in a local context that can be applied in learning Social Geography